Answer: JL=50
Explanation:
Step 1: The midpoint of a segment divides the segment into 2 congruent segments, which means JK=KL. SInce JK=KL, we know that 6x+7=9x-2.
Step 2: We can find x by simplifying 6x+7=9x-2 by subtracting 6x from both sides, which equals 7=3x-2.
Step 3: We can then simplify the equation even more by adding 2 to both sides. From this, we get 9=3x.
Step 4: To solve for x, we divide both sides by 3, which means that x=3.
Step 5: Since K is the midpoint of JL, we know that JK=KL. We can substitute JK for KL, so that JK+JK=JL. This means that (6x+7)+(6x+7)=JL.
Step 6: Since we know x=3, we can substitute 3 for x in (6x+7)+(6x+7)=JL, which would mean the equation is now (6(3)+7)+(6(3)+7)=JL.
Step 7: (6(3)+7)+(6(3)+7)=50
Step 8: JL=50